Chivalry, Reading, and Women's Culture in Early Modern Spain : From Amadís de Gaula to Don Quixote - Triplette, Stacey Elizabeth (Book collections on Project MUSE., 2018)
The Iberian Chivalric romance has long been thought of as an archaic, masculine genre and its popularity as an aberration in European literary history. 'Chivalry, Reading, and Women's Culture in Early Modern Spain' contests this view, arguing that the surprisingly egalitarian gender politics of Spain's most famous romance of chivalry has guaranteed it a long afterlife. 'Amadís' had a notorious appeal for female audiences, and the early modern authors who borrowed from it varied in their reactions to its large cast of literate female characters. 'Don Quixote', and other works that situate women as readers, carry the influence of 'Amadís' forward into the modern novel. This book analyses many versions of the romance from Spain, Portugal, France, Italy, and England and tells a new story of the life, death, and influences of 'Amadís'. When imitators and translators read chivalric romance, they also read gender, harnessing the female characters of the source text to a variety of political and aesthetic purposes.